Evaluating the Economic Impacts of Artificial Intelligence Integration on Supply Chain Management; A Mediation Analysis through AI Capability - Mohamad, Balouza (Journal of Ecohumanism, 2024)
The objective of this study was to assess the correlation between Artificial Intelligence (AI) and the performance of Supply Chain Management (SCMP) while also investigating the mediating influence of AI Capability (AICAP). The hypotheses examined were as follows: H1, the beneficial influence of AI on SCMP; and H2, the mediating role of AICAP in the link between AI and SCMP. The research was underpinned by a positivist philosophy which supported in being able to carry out an objective analysis of AICAP’s mediation between AI and SCMP. Regression analysis with a deductive way was used to investigate the relationship between independent and dependent variables. The ability to quantitatively analyze the data supported a comprehensive examination of hypotheses originally posited. Findings indicated that there is a strong positive association (r = 0.816) between AI and SCMP, with R2 of the variance in SCMP accounted by AI as 66.5%, therefore, continued support for H1 was established. Moreover, the mediating role of AICAP is significant (total effect = 0.8239 and mediation effect = 0.1862, implicating H2 as well. These results verify the importance of AI for SCMP improvement.